2011
DOI: 10.1002/jbmr.1503
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific changes in bone microarchitecture, mineralization, and stiffness during lactation and after weaning in mice

Abstract: Despite the dramatic bone loss that occurs during lactation, bone mineral density rapidly recovers after offspring are weaned and milk production stops. The goal of this study is to quantify site-specific changes in bone quantity and quality during and after lactation in a mouse model. We used micro computed tomography (mCT), individual trabecula segmentation (ITS), digital topological analysis (DTA)-based tissue mineral density (TMD) analysis, and micro finite element analysis (mFEA) to quantify the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
75
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 43 publications
10
75
0
Order By: Relevance
“…The tibiae and femora show similar changes in trabecular bone, while cortical bone displays reductions in cortical thickness, cross-sectional area, and tissue mineral density, and an increase in cortical porosity and endosteal perimeter (35, 101,566,580). However, another microCT study from the same investigators found no significant change in cortical parameters in the femora except for an increase in tissue density (34), while a peripheral QCT (pQCT) study found that lactation increased tibial mid-shaft cortical width, area, periosteal circumference, and cross-sectional moment of inertia in frontal, sagittal, and torsional planes (772).…”
Section: Animal Datamentioning
confidence: 99%
“…The tibiae and femora show similar changes in trabecular bone, while cortical bone displays reductions in cortical thickness, cross-sectional area, and tissue mineral density, and an increase in cortical porosity and endosteal perimeter (35, 101,566,580). However, another microCT study from the same investigators found no significant change in cortical parameters in the femora except for an increase in tissue density (34), while a peripheral QCT (pQCT) study found that lactation increased tibial mid-shaft cortical width, area, periosteal circumference, and cross-sectional moment of inertia in frontal, sagittal, and torsional planes (772).…”
Section: Animal Datamentioning
confidence: 99%
“…(10) Studies in rodent species variously report reversibility, partial or no reversibility after weaning. (13)(14)(15)(16)(17)(18) While trabecular bone is remodeled in rodents, rodents continue to grow throughout life and do not remodel cortical bone, or do so to a limited degree late in life. The synthesis of new trabeculae during continued growth may explain why the loss of trabecular bone is reversible.…”
Section: Journal Of Bone and Mineral Researchmentioning
confidence: 99%
“…Studies in rodent and other animal models demonstrate that trabeculae perforate, their numbers decrease, and cortical porosity increases. (10)(11)(12)(13)(14)(15)(16)(17)(18) This structural deterioration has been reported to be reversible in some animal models. (7,17,18) Bone loss during breastfeeding in humans is reported, but whether the microstructural deterioration is reversible after cessation of breastfeeding in human subjects is uncertain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This loss is reversed completely after weaning. For this reason, the weaning phase is considered the most anabolic phase in the reproductive cycle of a rodent and provides a vital window for the identification of new anabolic targets (7)(8)(9). For example, elevated levels of the neurohypophyseal hormone oxytocin during lactation and weaning led us to examine its action on bone (10,11).…”
mentioning
confidence: 99%